2011
DOI: 10.2135/cropsci2010.05.0296
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Normalized Difference Vegetation Index and Visual Quality in Turfgrasses: Effects of Mowing Height

Abstract: Canopy spectral reflectance may provide an objective means to evaluate visual quality of turfgrass, but evaluations of quality may be confounded by cultural practices that affect reflectance, such as mowing height. In this 2‐yr study near Manhattan, KS, we examined effects of mowing height on relationships between normalized difference vegetation index (NDVI) and visual quality ratings in Kentucky bluegrass (KBG; Poa pratensis L., ‘Apollo’) and in a KBG × Texas bluegrass (Poa arachnifera Torr.) hybrid (HBG; ‘T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 26 publications
9
41
0
Order By: Relevance
“…X C. transvaalensis Burtt Davy, 'Midiron']. In other studies, vegetation indices calculated from reflectance data were also strongly correlated with visual quality in a number of turfgrass species and under different cultural practices (Bell et al, 2002;Fitz-Rodriguez and Choi, 2002;Keskin et al, 2008;Lee et al, 2011).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…X C. transvaalensis Burtt Davy, 'Midiron']. In other studies, vegetation indices calculated from reflectance data were also strongly correlated with visual quality in a number of turfgrass species and under different cultural practices (Bell et al, 2002;Fitz-Rodriguez and Choi, 2002;Keskin et al, 2008;Lee et al, 2011).…”
mentioning
confidence: 89%
“…In fact. Lee et al (2011) compared models between two turfgrass species over 2 yr and reported that the models were different between species and between years within each species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…30-0.40. ) Most vegetation indices in turfgrasses have been developed using multispectral, or broadband, radiometry (Trenholm, Carrow, and Duncan 1999;Jiang and Carrow 2007;Bremer et al 2011aBremer et al , 2011bLee et al 2011), including in the study described above by Lee (2008). Multispectral radiometry measures the spectral reflectance of plant canopies in a few bands (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The variations in model strength and viability may be related to changes in the density of Kentucky bluegrass during the growing season. For example, in the study area the green biomass of Kentucky bluegrass typically increases during early spring but may decrease during middle to late summer when it is under heat stress (Bremer et al 2006;Lee et al 2011). There may be additional, poorly understood factors of the turfgrass canopy that change over the course of the growing season (e.g.…”
mentioning
confidence: 99%